1967
DOI: 10.1002/cne.901300405
|View full text |Cite
|
Sign up to set email alerts
|

Unit analysis of the pretectal nuclear group in the rat

Abstract: Unit responses to visual stimuli in the pretectal region of the rat were investigated with steel microelectrodes. Most units could be classified into two broad categories; "phasic" (brief on and off discharges) and "tonic-on" (sustained discharge during the visual stimulus). The responsive region appears to be coextensive with the n. praetectalis anterior (Pta) which can be divided into a dorsal portion containing "phasic" units and a ventral portion containing "tonicon" units. The projection of the contralate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1968
1968
1983
1983

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Yet Siminoff et al [1967b] have apparently described receptive field characteristics of single cells in the pretectal complex of the rat after removing part of the striate cortex. Since the cortex probably sends a topographically organized projection to the region, it would be of interest to know what the cortex may contribute to the very characteristics they were describing.…”
Section: Significance Of Topographic Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet Siminoff et al [1967b] have apparently described receptive field characteristics of single cells in the pretectal complex of the rat after removing part of the striate cortex. Since the cortex probably sends a topographically organized projection to the region, it would be of interest to know what the cortex may contribute to the very characteristics they were describing.…”
Section: Significance Of Topographic Organizationmentioning
confidence: 99%
“…By contrast, Siminoff et al [1967b] identified sev eral classes of single units in the pretectal complex of the rat; one type of unit was characterized by very large receptive fields and a tonic discharge that did not habituate, and Sim in o ff et al suggest that this population may mediate the pupillary light reflex. More important, in both species a majority of the units in the pretectal complex respond maximally to mov ing stimuli and many are directionally selective.…”
mentioning
confidence: 99%
“…In the course of our investigations of the retinotopic projection to the rat colli culus, we were surprised to find a discordant pattern in electrode penetra tions through the rostral pole. A more detailed analysis [Siminoff, Schwassmann and Kruger, 1967] revealed a crude but distinct topo graphic pattern ( fig. 4) within the principal or anterior pretectal nucleus, and that the physiological properties of neural elements in this nucleus were different from the features disclosed for other visual structures.…”
mentioning
confidence: 99%
“…Humphrey [1968], however, found no evidence of directional selectivity in units recorded from the superior colliculus of the rat or monkey although Simonoff, Schwassman and Kruger [1967] reported directional units in the rat pre-tectum. We have found no directionally selective units in the optic nerve, contralateral tectum or ipsilateral tectum of the frog.…”
Section: Resultsmentioning
confidence: 93%
“…In the superior colliculus of many vertebrate species a proportion of the visually activated units are directionally selective (goldfish: Cronly-Dillon [1964], Jacobson and Gaze [1964]; pigeon: Maturana and Frenk [1963]; rabbit: Hill [1966]; cat: Marchiafava and Pepeu [1966], Straschill and Taghavy [1967], Mcllwain and Buser [1968], Sterling and Wickelgren [1969]; squirrel: Michael [1967]). Humphrey [1968], however, found no evidence of directional selectivity in units recorded from the superior colliculus of the rat or monkey although Simonoff, Schwassman and Kruger [1967] reported directional units in the rat pre-tectum. We have found no directionally selective units in the optic nerve, contralateral tectum or ipsilateral tectum of the frog.…”
Section: Resultsmentioning
confidence: 94%